Performance Modeling and Analysis of Secure Registration Process of CPEs in IEEE 802.22 WRAN Cognitive Radio Network - Afzal, H.; Mufti, M. R.; Ahmed, K. T.; Rehman, M.; Yousaf, M.; Qaseem, D. (The Nucleus, 2021)
The proliferation of wireless technologies has affected the radio frequency spectrum which is a limited natural resource. Increase in the development of diverse wireless technologies is creating a spectrum shortage problem. The usage of radio frequency spectrum is not uniform because, some of the licensed spectrums remain vacant most of the time. A cognitive radio (CR) is one of the solutions to address this problem. Meanwhile, the popularity of cloud computing has attracted the researchers to get its benefits for the efficient utilization of cognitive radio networks (CRNs). Both of these technologies can be integrated to form a new type of network called cognitive radio cloud network in which security is one of the major issues in CRNs. This paper presents the analytical framework to perform analysis of the registration process of Customer Premises Equipment (CPE) with the base station in Wireless Regional Area Network (WRAN) in addition of the cloud platform for applying the security. The performance is investigated by comparing the scenarios of keeping the security features on and off in the system. The numerical results confirm that the proposed system works well, when security is kept on.